Efficacy of Some Herbicides on Growth, Tuber Production and Viability of Purple Nut-sedge (Cyperus rotundus L.)* - Mohamed, Mohamed Abdel Halim; Ali, Eltom E.; Elamin, Salah E. (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted at the Sugarcane Research Center, Guneid, during 2004/05 and 2005/06 seasons to evaluate the efficacy of some foliar herbicides on the growth of purple nutsedge (Cyperus rotundus L.) and to assess the effect of the treatments on the production and viability of tubers. The products tested were Krismat 75 WG (Trifloxysulfuron-sodium+ametryn) at three rates (1.79, 2.38 and 2.98 kg product ha-1 ) and Envoke 75 WG (Trifloxysulfuron-sodium) at three rates (0.025, 0.030 and 0.035 kg product ha-1 ). Ametryn (Gesapax 50 FW) + Atrazine (Gesaprim 50 FW) were used at the recommended rates (3.81 L + 3.81 L product/ha), as a control. The results showed that statistically significant control of purple nut-edge was attained by all chemical treatments compared with the untreated check. Envoke 75 WG at 0.035 kg product/ha and the standard mixture of Gesapax + Gesaprim at its recommended rate significantly (P=0.05) reduced the number of purple nut-sedge compared with the untreated check. Gesapax + Gesaprim gave the lowest number of green leaves per plant. Envoke 75 WG and Krismat 75 WG showed consistent reductions in tuber production and sprouting. Therefore, their successive application may lead to persistence and continuous reduction in the population density of purple nut-sedge in the fields of sugarcane.